Technology and human resource management: Some observations - Shrestha, Prakash (NCC Journal, 2021)
This paper aims to explore some impact of technology on human resource management. It also observes some recent technological trends that redefine human resource management. This paper mainly reviews and describes scholarly papers, articles, professional research work, and research reports of different national and international organizations to observe the impact of technology on human resource management and some recent technological trends that redefine human resource management as well. It is found that the areas of human resource management where technology has a significant impact include recruiting, employee selection, training and development, ethics and employee rights, motivating knowledge workers, pay plans and employee benefits, communication, decentralized work site, skill levels, and legal concern. Today’s business organizations also need to focus on some recent technological trends (such as big data, mobile apps, social media, cloud technology and SaaS, and wearable technology) that redefine human resource management.